2018
DOI: 10.1155/2018/7462101
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer: How Familiar Are Our Future Doctors with the Cancer of Tomorrow?

Abstract: Background Colorectal cancer (CRC) is one of the common cancers affecting both genders. Although the incidence of CRC is low in India there has been an increase in the past few decades. Objective To assess the awareness regarding colorectal cancer and its screening among medical students and interns. Methods This cross-sectional study was conducted among 290 participants (final year medical students and interns) from Kasturba Medical College, Mangalore. A pretested semistructured questionnaire was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…As shown in the Table 5 the knowledge gap between medical and non-medical is signi cant; however, in some aspects such as epidemiology or personalised approach to the patients could be improved. Similar conclusions were presented by researchers from other countries 22,31,32,46,47 . On the other hand, various studies from the Middle East underline limited knowledge and poor attitudes towards CRC screening among medical students 10,48,49 .…”
Section: Discussionsupporting
confidence: 89%
“…As shown in the Table 5 the knowledge gap between medical and non-medical is signi cant; however, in some aspects such as epidemiology or personalised approach to the patients could be improved. Similar conclusions were presented by researchers from other countries 22,31,32,46,47 . On the other hand, various studies from the Middle East underline limited knowledge and poor attitudes towards CRC screening among medical students 10,48,49 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, planning to pursue a surgical specialty was significantly associated with having a high level of knowledge about gastric cancer prevention (aPR: 1.43, 95%CI: 1.13-1.81; p=0.003). In this regard, Kulkarni et al, 20 in a research conducted on 290 participants, including interns and final year medical students (making it clear that the latter were included because they had already completed the surgical theory courses and the clinical internship component) from the Kasturba Medical College, Mangalore, reported that 22.8%, 68.3% and 0.90% of last-year medical students exhibited an excellent, good and poor level of knowledge on colorectal cancer prevention, respectively. Therefore, it seems that completion of surgical theory courses and opting for a surgical specialty are factors that could contribute to a better understanding of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, widespread screening and technical expertise for CTC is inadequate in India, resulting in advanced disease stage at presentation. 100,101 B. Gastric Cancer Definition, Prevalence in India As per the National Cancer Registries (NCR)population-based tumor registries and Hospitalbased cancer registries, the prevalence of gastric cancer (GC) ranges from 0.5/100,000 in Western India to 12.2/100,000 in Southern to 64.2/100,000 in Eastern Indian population. 102 Thus, though the prevalence of gastric cancer is low compared to Western counterparts, there is immense regional diversity.…”
Section: Challenges In Diagnosis and Treatmentmentioning
confidence: 99%